2004
DOI: 10.1002/chin.200442111
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Sonogashira Coupling Reactions in an Ionic Liquid, Effected in the Absence of Both a Copper Salt and a Phosphine.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 1 publication
2
11
0
Order By: Relevance
“…All samples showed well-developed (001) Bragg reflections at 2θ = 20.1°, which indicated that such clay material maintains good crystallinity . In Figure b, the characteristic diffraction of Pd(111) shifts to 2θ = 41° which was slightly different from the reported value (Pd(111) 2θ = 40.1°) .…”
Section: Resultsmentioning
confidence: 73%
“…All samples showed well-developed (001) Bragg reflections at 2θ = 20.1°, which indicated that such clay material maintains good crystallinity . In Figure b, the characteristic diffraction of Pd(111) shifts to 2θ = 41° which was slightly different from the reported value (Pd(111) 2θ = 40.1°) .…”
Section: Resultsmentioning
confidence: 73%
“…The widespread interest of ionic liquids (ILs) in catalysis , and our continued search for new alternatives for selective organic transformations prompted us to investigate these important reactions using ILs. , Recently, ionic liquids have been reported to mediate the ring opening of epoxides with amines, although longer reaction times are required . Herein, we also report the regioselective ring opening of epoxides with amines to produce the corresponding β-amino alcohols in high yields using a recyclable catalytic system (Cu(acac) 2 immobilized in ionic liquids; see Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Starting from the mesityl complexes 1a, 1b, 1e, and 1f as well as from [(IiPr Me )Cu(Mes)] (1c) reported previously, the The exchange of the mesityl ligand by a fluoride ion to yield 2a−2e can be followed easily in the 19 F NMR spectra as these complexes show a single resonance for the fluorido ligand in the range of −237 to −253 ppm (2a: −252.7 ppm, 2b: −240.3 ppm, 2c: −241.8 ppm, 2e: −236.9 ppm). Furthermore, the complexes 2a−2f are of considerable interest, attributed to the inherent instability of CuF as a discrete molecular entity beyond the gas phase, leading to its disproportionation into CuF 2 and metallic Cu.…”
Section: Synthesis Of [(Nhc)cuf] and [(Caac Me )Cuf]mentioning
confidence: 99%